Edukasi Mengenai Kebersihan Genitalia Pada Remaja Awal di SMPK Kusuma Mataram: Counseling and Mangrove Planting - FINSDV; FAADV; Hidajat, Dedianto; Wedayani, Anak Agung Ayu Niti; Putri, Novia Andansari (Universitas Mataram, 2024)
Sekotong Tengah is one of the areas that has a Mangrove ecotourism attraction. The mangrove ecosystem is one of the natural resources that is very important for the survival of humans, as well as its role and function in maintaining ecological balance in coastal areas. The stages that must be carried out for mangrove ecosystem rehabilitation include (1) Location Identification; (2) Seed Identification; (3) Determining Planting Season; (4) Determining Planting Patterns; (5) Conducting Planting; (6) Monitoring. The KKN-PMD UNRAM group in Sekotong Tengah provides counseling and conducts mangrove planting with the aim and benefits of raising awareness about the importance of coastal ecosystems, especially mangroves, providing knowledge about how to plant mangroves, building community awareness to pay more attention to the environment and preserve ecosystems. One of the activities that can preserve the mangrove ecosystem as an effort in developing the ecosystem of Sekotong Tengah village.